RESPIRATORY ILLNESS AND RESPIRATORY SYNCYTIAL VIRUS (RSV)-RELATED HOSPITALIZATION (RSVH) IN INFANTS WITH CONGENITAL AIRWAY ANOMALIES (CAA) IN THE CARESS REGISTRY (2005-2015). (26th May 2017) - Wong, S; Paes, B; Li, A; Mitchell, I; Lanctôt, K L
Abstract: BACKGROUND: RSV is the primary cause of lower respiratory tract viral infections in children <2 years of age. Infants with congenital airway anomalies (CAA) may experience increased risk of respiratory illness-related hospitalization (RIH) and RSV-related hospitalization (RSVH). The Canadian RSV Evaluation Study of Palivizumab (CARESS) tracks outcomes following palivizumab prophylaxis in high-risk infants. OBJECTIVES: We compared the hazard for RIH and RSVH in infants with CAA versus those prophylaxed with palivizumab for other serious underlying medical disorders (MD) or for standard indications (SD). DESIGN/METHODS: Data was assembled from the CARESS registry, a prospective, observational, cohort study of children who received ≥1 injection of palivizumab across 32 Canadian hospital sites. Neonatal and demographic data were collected upon enrolment. Post-injection telephone surveys were conducted monthly to assess palivizumab utilization and adherence, including outcomes related to respiratory infection events. RESULTS: 21, 436 infants were enrolled (850 CAA, 2982 MD, and 17, 604 SD). Statically significant demographic differences (p<0.05) across groups were found in: enrolment and gestational age, birth and enrolment weight, as well as proportions of Caucasians, daycare attendance, exposure to smoking, siblings, multiple birth status, household crowding, and family history of atopy. Overall palivizumab adherence with inter-dose intervals was 72.3% and was similar across indications. 1501 infants were hospitalized a total of 1800 times. CAA infants had a RIH rate of 11.6% (MD [10.1%], SD [6.3%]) with a significantly increased hazard compared to MD (HR = 1.41, 95%CI 1.14-1.75, p=0.002) and SD (HR = 1.22, 95%CI 1.06-1.39, p=0.005). Crude RSVH rates were: 1.65% (CAA) versus 1.58% (MD), 1.34% (SD). By Cox proportional hazard analysis, CAA infants had similar RSVH hazard versus MD or SD infants (χ 2 =0.65, df=2, p=0.72). After adjusting for daycare attendance, siblings, smoking exposure, crowding, and atopy, the model was significant (χ 2 =66.5, df=5, p<0.0005); however, based on indications for palivizumab the model was found to be insignificant (p=0.92). CONCLUSION: CAA infants experienced increased RIH risk relative to MD and SD infants. However, hazard for RSVH appeared to be similar across indications which may be due to the smaller CAA sample size compared to MD and SD.